An Analysis of Indonesian Islamic Higher Education Institutions in the Era of Globalization - Achruh, Achruh; Sukirman, Sukirman (International Journal of Learning, Teaching and Educational Research, 2024)
This study aims to explore how globalization and religious conservatism shape institutional and individual identities within Indonesian Islamic Higher Education Institutions (IHEIs). Data were collected through in-depth semi-structured interviews with 30 experienced scholars, selected using purposive sampling from various IHEIs across Indonesia. The study found that globalization is perceived as a double-edged sword, offering opportunities for knowledge expansion and intercultural dialogue while also raising concerns about the erosion of cultural and religious identity. Religious conservatism manifested in a spectrum of responses, from traditionalist interpretations of Islam to advocacy for progressive and inclusive approaches. Participants’ responses varied, demonstrating IHEI agency in adapting curricula to integrate modern subjects while safeguarding Islamic principles. The study also highlighted individual agency within IHEIs, where scholars navigate personal beliefs and institutional expectations, advocating for social change within the boundaries of cultural and religious norms. However, this agency is often constrained by institutional structures and societal pressures. These findings underscored the need for context-specific policies that acknowledge diversity within IHEIs and empower both institutions and individuals to navigate the complexities of globalization and religious conservatism while preserving their unique identities. https://doi.org/10.26803/ijlter.23.9.5